2015
DOI: 10.1016/j.jphys.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The Manual Diaphragm Release Technique improves diaphragmatic mobility, inspiratory capacity and exercise capacity in people with chronic obstructive pulmonary disease: a randomised trial

Abstract: NCT02212184.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 21 publications
7
91
0
18
Order By: Relevance
“…Furthermore, there have only been a limited number of studies investigating the effect of diaphragmatic manipulation in the presence of respiratory diseases such as COPD. 23,24 In a recent review paper, Heneghan and colleagues 24 concluded there is currently no evidence to support or reject the use of manipulative therapy for improving lung function in patients with COPD. This view is contradicted by Wearing et al with respect to spinal manipulative therapy and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there have only been a limited number of studies investigating the effect of diaphragmatic manipulation in the presence of respiratory diseases such as COPD. 23,24 In a recent review paper, Heneghan and colleagues 24 concluded there is currently no evidence to support or reject the use of manipulative therapy for improving lung function in patients with COPD. This view is contradicted by Wearing et al with respect to spinal manipulative therapy and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…We understand the strategic importance of the function of the diaphragm muscle on circulatory function and we know that if approached using manual techniques it can improve its function and excursions, with benefits to all bodily systems [30,31]. We know that the pelvic floor if treated using osteopathic methods, it's functional ability is improved [32].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on COPD patients showed that parameters such as mobility, exercise capacity, maximal respiratory pressure, and vital capacity were improved by working the anterior chondrocostal arch with the manual diaphragm release technique [29].…”
Section: Physiotherapy Manual Therapy and The Diaphragmmentioning
confidence: 99%